Perancangan Sistem Pengukuran Kinerja Organisasi Non Profit (Studi Kasus pada UTDC PMI Surakarta) - Jauhari, Wakhid Ahmad; Liquiddanu, Eko; Nugraheni, Eka Agustina (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2010)
In this paper we developed performance measurement system in UTDC PMI Surakarta. We used Integrated Performance Measurement System (IPMS) methodology which based on stackeholder’s requirement, to design the measurement system. From the design process, it can be identified 8 stakeholders, and based on stakeholder’s requirements, it can be obtained 27 requirements and 7 objectives. Furthermore, we developed 19 key performance indicators (KPIs) which can be classified into 6 aspects, including donor, human resources, blood preparation, output, administration, and control and evaluation.Finally, we conducted Analythic Hierarchy Process (AHP) method to weight the all aspects and KPIs. It was found that human resources(0.435) was most importance aspect and employee’s performance achievement (0.24) became most importance indicator among them.